2014
DOI: 10.1017/s0954579414000261
|View full text |Cite
|
Sign up to set email alerts
|

Relational victimization, friendship, and adolescents' hypothalamic–pituitary–adrenal axis responses to an in vivo social stressor

Abstract: Adolescents’ peer experiences may have significant associations with biological stress-response systems, adding to or reducing allostatic load. This study examined relational victimization as a unique contributor to reactive hypothalamic–pituitary–adrenal (HPA) axis responses as well as friendship quality and behavior as factors that may promote HPA recovery following a stressor. A total of 62 adolescents (ages 12–16; 73% female) presenting with a wide range of life stressors and adjustment difficulties comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 87 publications
4
50
0
Order By: Relevance
“…The association between not having a best friend and the increased overall cortisol daily output in females is in line with the hypotheses of the ameliorative effects of friendships in the context of stress ( 28 ). Likewise, substance use has also been associated with altered cortisol profiles in adolescence ( 29 ).…”
Section: Discussionsupporting
confidence: 85%
“…The association between not having a best friend and the increased overall cortisol daily output in females is in line with the hypotheses of the ameliorative effects of friendships in the context of stress ( 28 ). Likewise, substance use has also been associated with altered cortisol profiles in adolescence ( 29 ).…”
Section: Discussionsupporting
confidence: 85%
“…The only time that differs is the five minutes of speech preparation when the participant is either with the parent or the friend and the time during the speech and math when the participant is alone with the assessors. Interestingly, social buffering effects have been observed when the supportive figure is present before, during, and after the stressor (e.g., Calhoun et al, 2014; Coan, Schaefer, & Davidson, 2006; Hostinar et al, 2015), but the time course of these effects (reactivity vs. recovery) likely differs depending on the timing of supportive figure’s presence.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that, across participants, children demonstrated lower cortisol levels after a negative event when they reported being with their best friend relative to negative events without their best friend present (Adams, Santo, & Bukowski, 2011). There is also evidence that when allowed to debrief with a friend, 12- to 16-year-olds who had good quality relationships with the friend who debriefed them returned to baseline faster following a social evaluative stressor than did same-aged youth who had poor relationships with the friend who debriefed them (Calhoun et al, 2014). Of course, in both of these cases it could be that being the type of individual who can develop and maintain high quality friendships might be associated with characteristics that make one more stress-resilient.…”
mentioning
confidence: 99%
“…As intimacy has been described as a key feature of the social buffering of stress (Smith et al, 2009), it is plausible that friends rather than parents may be better at helping older adolescents return to baseline after initiation of the stress response. Indeed, a study of older adolescents ages 12–16 revealed that recovering from a stressor with a friend who exhibited low negative qualities in the friendship was related to better HPA axis recovery (Calhoun et al, 2014). Our results suggest that the social changes associated with increasing age explain why parents were ineffective at helping to regulate the stress response for older adolescents in our sample.…”
Section: Discussionmentioning
confidence: 99%